Hospitals and the generic versus brand-name prescription decision in the outpatient sector - Gerald J. Pruckner; Thomas Schober (Johannes Kepler University Linz, Christian Doppler Laboratory Aging, Health and the Labor Market, 2016)
Healthcare payers try to reduce costs by promoting the use of cheaper generic drugs. We show that there are strong interrelations in drug prescriptions between the inpatient and the outpatient sector using a large administrative dataset from Austria. Patients with prior hospital visits have a significantly lower probability to receive a generic drug in the outpatient sector. The size of the effect depends on both patient and doctor characteristics which can be related to differences in hospital treatment and heterogeneity in physicians' adherence to hospital choices. The spillover effects create cost ineffectiveness, in particular in healthcare systems with separate funding of inpatient and outpatient service provision.
Keywords: I11; 330; prescription decision; generic drugs; physician behavior; hospitals